Application of Ice Breaking in Increasing The Concentration of Female Futsal Athletes - Oktrina, Trias Kartika; Perwira Bakti, Ananda; Pudjijuniarto, Pudjijuniarto; Fithroni, Hijrin (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
Futsal sports revealed that the ice breaking technique was effective in increasing the concentration of female futsal athletes at the El-Wafa Airwomen club. This research aims to determine whether ice breaking techniques can increase the concentration of female futsal athletes from the Airwomen El-Wafa club. The research method used was descriptive quantitative with a one group pretest-posttest experimental design, involving 20 athletes as samples. The ice breaking that is implemented includes gathering games, counting, shouting "bang", and tic tac toe drills for 7-15 minutes in between training sessions. Data was collected via questionnaire and analyzed using descriptive techniques, normality test, and paired sample T-test. The results of the analysis show that before the implementation of ice breaking, the average athlete concentration value was 51.95, which is quite good with a percentage of 35%. After implementation, the average score increased significantly to 71.10, which is included in the very good category with a percentage of 45%. The Paired Sample T-test showed a significant increase in concentration with a difference of 19.15 points between the pretest and posttest. These findings prove that the ice breaking technique can substantially optimize athletes' concentration and response during training, increase creativity in problem solving and preparedness in tactical and strategic training. Thus, the application of ice breaking is an effective strategy to improve the quality of training and performance of female futsal athletes at the El-Wafa Airwomen club.